2018
DOI: 10.1101/388645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real-time analysis of the diphtheria outbreak in forcibly displaced Myanmar nationals in Bangladesh

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This definition may be practically relevant in a range of scenarios. For example, real-time analysis of a diphtheria epidemic in Cox Bazar's in Bangladesh involved assessing the number of hospital beds that were needed [46]. The number of beds required was approximated in that study by using a model to forecast disease incidence, assuming that 15% of reported cases would require treatment as inpatients with an average hospital stay of five days for each case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition may be practically relevant in a range of scenarios. For example, real-time analysis of a diphtheria epidemic in Cox Bazar's in Bangladesh involved assessing the number of hospital beds that were needed [46]. The number of beds required was approximated in that study by using a model to forecast disease incidence, assuming that 15% of reported cases would require treatment as inpatients with an average hospital stay of five days for each case.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the ongoing COVID-19 pandemic, one of the main aims of interventions in the UK has been to ensure that the number of individuals requiring intensive care unit beds remains below the total number of beds available [43][44][45]. More generally, the threshold capacity might derive from the number of available beds in hospitals or treatment units [46,47], or the availability of care workers [48]. This motivates consideration of the "concurrent size" metric above.…”
Section: Durationmentioning
confidence: 99%
“…Humanitarian needs assessments can be more climateinformed by including a review of the latest vulnerability and adaptation assessment or the Health National Adaptation Plan (H-NAP) as a component of their contextual assessment. Other useful resources include the UNFCCC -WHO Health and Climate Change Country Profiles that documents priority climate change and health impacts, how they are projected to develop according to different climate scenarios, and what actions are being planned or undertaken to address them [27].…”
Section: Climate-informed Humanitarian Needs Assessmentmentioning
confidence: 99%
“…1,2 Even though diphtheria can be prevented by immunization, it remains a major health problem in developing countries such as India, Thailand, and Bangladesh. [3][4][5] During an outbreak, the emergency department (ED) has an important role in identifying suspected cases and providing acute medical management, while controlling infection transmission. It needs to act fast by implementing the World Health Organization (WHO) guidelines for suspected infectious disease.…”
Section: Introductionmentioning
confidence: 99%